2012
DOI: 10.1542/peds.2011-2281
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Replacement Therapy During Pregnancy and Infantile Colic in the Offspring

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Infantile colic affects almost 10% of all infants and is characterized by crying and fussing in an otherwise healthy and well-fed infant. Prenatal exposure to tobacco smoking is a risk factor, but it is unclear whether nicotine causes the association.WHAT THIS STUDY ADDS: Infants exposed to nicotine replacement therapy during pregnancy had elevated infantile colic risk of the same magnitude as infants exposed to tobacco smoking. Intrauterine exposure to nicotine may play a causal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 35 publications
(35 reference statements)
0
31
0
Order By: Relevance
“…Another study (Dhalwani et al (2015), CAF 9, “fair”) used mother–child primary care records of children born in the UK to relate NRT prescription to incidence of major congenital abnormalities. The remainder (Lassen et al (2010); Milidou et al (2012); Morales-Suarez-Varela et al (2006); Strandberg-Larsen et al (2008); Torp-Pedersen et al (2010); Zhu et al (2014), CAFs 2 to 7, all “good”) derived from the Danish National Birth Cohort, each concerning different endpoints. The analyses all involve births in 1996 to 2003, though the publications vary in inclusion/exclusion criteria, and the comparison groups used for assessing NRT effects, some only reporting risks for women who used NRT and did not smoke.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study (Dhalwani et al (2015), CAF 9, “fair”) used mother–child primary care records of children born in the UK to relate NRT prescription to incidence of major congenital abnormalities. The remainder (Lassen et al (2010); Milidou et al (2012); Morales-Suarez-Varela et al (2006); Strandberg-Larsen et al (2008); Torp-Pedersen et al (2010); Zhu et al (2014), CAFs 2 to 7, all “good”) derived from the Danish National Birth Cohort, each concerning different endpoints. The analyses all involve births in 1996 to 2003, though the publications vary in inclusion/exclusion criteria, and the comparison groups used for assessing NRT effects, some only reporting risks for women who used NRT and did not smoke.…”
Section: Resultsmentioning
confidence: 99%
“…a ReferencesComparison b Endpoint c Cases d OR/RR (95 %CI) e 5Torp-Pedersen et al (2010)Any NRT versus no NRTStrabismus61/12391.22 (0.92–1.61) f 6Milidou et al (2012)Any NRT versus no NRTInfantile colic137/14171.15 (0.97–1.37) g 7Zhu et al (2014)Any NRT versus no NRTADHD29/5321.11 (0.75–1.63) h HISNA−0.08 (−0.28 to 0.12) i 11Kapur et al (2001)Nicotine versus placebo patchRapid fetal movements0/10.24 (0.01–5.38) j 12Schroeder et al (2002)Nicotine patchSevere infant morbidity3/−No comparison group13Pollak et al (2007)Any NRT + CBT versus CBT onlyAny serious AE34/101.75 (0.93–3.28) j Placental abnormality4/04.64 (0.25–84.7) j 14Oncken et al (2008)Nicotine versus placebo gumMaternal hospitalization9/81.01 (0.41–2.50) j Spontaneous abortion2/04.49 (0.22–92.19) j Any serious AE24/33…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional question to ask is whether these convergent deficiencies in neural structures place infants at greater risk of exhibiting emotional and behavioral problems at later ages. Toward that end, we note that Milidou, Henriksen, Jensen, Olsen, and Søndergaard () found that children with a history of infantile colic had a slightly increased probability of exhibiting emotional and conduct problems, attention‐deficit/hyperactivity disorder, and difficult relations with peers in comparison to children who did not have a history of colic. That adolescents who had infantile colic demonstrate greater problems controlling and integrating emotions, attention, and self‐regulation could reflect a continuing decrement in functionality at the ACG level although, given the maturity of chemoreceptors as a backup for the reinitiation of breathing, the consequences would no longer be life threatening (SIDS) but find expression in different ways.…”
Section: Switching the Subject: Task Switching What Is The Connection?mentioning
confidence: 84%
“…This has led some practitioners to advocate the use of nicotine replacement therapy (NRT) as a smoking cessation aid for pregnant women since it may reduce the risk of low birth weight and preterm delivery [8]. However, the clinical community is divided on this recommendation because of continued concerns about efficacy and safety [9,10]. Preclinical investigators have long argued that nicotine is a developmental teratogen and should not be used as a treatment for pregnant smokers [2,11].…”
Section: Future Directionsmentioning
confidence: 99%